33. NORMA REGIONAL DAN PERUBAHAN KEBIJAKAN MYANMAR DALAM MENANGANI KEJAHATAN PERDAGANGAN NARKOBA - Muhamad Iksan; Hermini Susiatiningsih; Mohammad Rosyidin (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
In the past few decades, The Golden Triangle, consist of Myanmar, Thailand, and Laos,has been known as one of major drugs producers in the world. In 2000 ASEAN memberstates agreed to ratify the declaration of Drug-Free ASEAN 2015 as a mutual commitmentto eliminate the distribution and abuse of drugs in Southeast Asia. In Myanmar, the lack ofgovernment control and policy implementation during military regime had becameprimary factor that caused the stagnation of drugs policy in Myanmar. The military regimewhich ruled Myanmar for almost 50 years eventually ended and replaced by the civiliangovernment led by Thein Sein in 2011. Thein Sein carries reformative steps to solve sociopoliticproblems, including drugs policy at domestic level. This research aims to explainthis policy change. Using constructivist paradigm, this research argues that public policycan be affected by norms applied in the region. This research concludes that Myanmar’spolicy change under Thein Sein administration was influenced by the regional norm, thatis Drug-Free ASEAN 2015.